2022
DOI: 10.1007/s43630-022-00212-4
|View full text |Cite
|
Sign up to set email alerts
|

Searching for antimicrobial photosensitizers among a panel of BODIPYs

Abstract: In recent years, antimicrobial Photodynamic Therapy (aPDT) gained increasing attention for its potential to inhibit the growth and spread of microorganisms, both as free-living cells and/or embedded in biofilm communities. In this scenario, compounds belonging to the family of boron-dipyrromethenes (BODIPYs) represent a very promising class of photosensitizers for applications in antimicrobial field. In this study, twelve non-ionic and three cationic BODIPYs were assayed for the inactivation of Staphylococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Our results displayed higher biofilm inhibition activity than their findings. Orlandi et al 66 examined the antibiofilm activity of 3 cationic and 12 non‐ionic BODIPY compounds against S. aureus , C. albicans and P. aeruginosa . It was found that some of BODIPY compounds showed antibiofilm activity without light irridiation and also when light irridation exposed they indicated excelsior antibiofilm activity than dark application.…”
Section: Resultsmentioning
confidence: 99%
“…Our results displayed higher biofilm inhibition activity than their findings. Orlandi et al 66 examined the antibiofilm activity of 3 cationic and 12 non‐ionic BODIPY compounds against S. aureus , C. albicans and P. aeruginosa . It was found that some of BODIPY compounds showed antibiofilm activity without light irridiation and also when light irridation exposed they indicated excelsior antibiofilm activity than dark application.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, however, the importance of PS's binding to bacterial cells has not been confirmed. Among a series of neutral and cationic BODIPYs studied, even though the cationic ones showed a higher binding, unexpectedly, a neutral BODIPY molecule (B9) showed the strongest PDI effect against P. aeruginosa PAO1 24-h-old biofilm [126]. With 40 µM of B9, and after green light activation (520 nm; fluence rate 2.4 mW/cm 2 ; light dose 30 J/cm 2 ), a 5-log reduction of adherent and planktonic cells was reported [126].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 98%
“…BODIPY (4,4-difluoro-boradiazaindacene) dyes, first reported in 1968, are widely used as fluorescent probes to label biomolecules [20,21]. Recently, increasing attention has been focused on the photodynamic properties of BODIPY due to its large molar absorption coefficients, high fluorescence quantum yields, and tunable modifications [22][23][24]. Our previous studies reported a derivative of BODIPYs, named BDP-4L, as a promising Type II photosensitizer [25,26].…”
Section: Introductionmentioning
confidence: 99%